2021
DOI: 10.1177/15280837211000365
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behavior of functionally graded polymeric composite beams

Abstract: The bending test is one of the most important tests that demonstrates the advantages of functional gradient (FGM) materials, thanks to the stress gradient across the specimen depth. In this research, the flexural response of functionally graded polymeric composite material (FGM) is investigated both experimentally and numerically. Fabricated by a hand lay-up manufacturing technique, the unidirectional glass fiber reinforced epoxy composite composed of ten layers is used in the present investigation. A 3-D fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Those can be obtained from Refs. [ 40 , 41 ] and are tabulated in Table 4 . is a coefficient that determines the contribution of the shear stress to the fiber tensile initiation criterion.…”
Section: Methodsmentioning
confidence: 99%
“…Those can be obtained from Refs. [ 40 , 41 ] and are tabulated in Table 4 . is a coefficient that determines the contribution of the shear stress to the fiber tensile initiation criterion.…”
Section: Methodsmentioning
confidence: 99%
“…[38,39] Furthermore, the tensile strength of M2 was between that of M1 and M2 due to insufficient interfacial bonding between the layers owing to room temperature curing. As reported by Atta et al [40] and Othman et al, [41] volume percentage of filler at the top surface significantly improve the flexural strength of FGMs. Failure of samples in flexural loading undergoes various stages from bottom to top.…”
Section: Tensile Strengthmentioning
confidence: 53%
“…Figure 5A represents the flexural strength of pure epoxy and PFGMs samples. It was observed that flexural strength of epoxy enhanced with the incorporation of aluminum particles.As reported by Atta et al[40] and Othman et al,[41] volume percentage of filler at the top surface significantly improve the flexural strength of FGMs. Failure of samples in flexural loading undergoes various stages from bottom to top.…”
mentioning
confidence: 52%
“…Simply supported boundary conditions were employed at the support elements. When any component of the FRP tube in the model exceeds the corresponding maximum tensile stress limit of the material, the failure of the specimen was identified [ 42 ].…”
Section: Finite Element (Fe) Modellingmentioning
confidence: 99%